Pengaruh Otonomi Kerja Terhadap Turnover Intention Melalui Mediator Pemberdayaan Psikologis Pada Karyawan Pertelevisian - Akbar, Iqbal Bahtiyar; Hasanati, Nida; Shohib, Mohammad (Cognicia, 2019)
ABSTRACT Turnover Intention is an important phenomenon that affects the development of the company. One of the factors that influence turnover intention is work autonomy. High work autonomy will increase psychological empowerment, ultimately affecting turnover intention. The purpose of this study is to determine the effect of work autonomy on turnover intention through mediators of psychological empowerment. This research approach uses a quantitative approach. The method of data collection uses the scale of The Work Design Questionnaire, the Multidimentional questionnaire of Psychological Empowerment and Mobley's Measurement Model. Determination of the sample using purposive sampling technique, the total subject is 72 people from four local television companies in Malang, Data analysis using Bootstrapping analysis. The results obtained are (1) There is no effect of work autonomy on turnover intention, the value of F = 2.748 (p = 0.102); (2) There is an influence of work autonomy on psychological empowerment with a value of F = 47.07 (p = 0,0001); (3) There is no effect of psychological empowerment on turnover intention, F value = 0.654 (p = 0.421); (4) There is no mediating effect of psychological empowerment on work autonomy with turnover intention.KEYWORDS Turnover Intention, Work Autonomy, Psychology EmpowermetCITITATION  Akbar, I., Hasanati, N., & Shohib, M. (2019). Pengaruh Otonomi Kerja Terhadap Turnover Intention Melalui Mediator Pemberdayaan Psikologi Pada Karyawan Pertelevisian. Jurnal Online Psikologi,  7,  (3), X-X.